2017
DOI: 10.1155/2017/4751249
|View full text |Cite
|
Sign up to set email alerts
|

Divorce and Severity of Coronary Artery Disease: A Multicenter Study

Abstract: The association between marital status and coronary artery disease (CAD) is supported by numerous epidemiological studies. While divorce may have an adverse effect on cardiac outcomes, the relationship between divorce and severe CAD is unclear. We conducted a multicenter, observational study of consecutive patients undergoing coronary angiography during the period between April 1, 2013, and March 30, 2014. Of 1,068 patients, 124 (12%) were divorced. Divorce was more frequent among women (27%) compared to men (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…We hypothesised that MPF would be associated with midlife obesity, given that it often involves an early age at first birth, high parity and multiple partnership dissolution—three factors that have been found to be independently associated to BMI as part of cardiovascular risk [ 8 , 9 , 11 , 26 , 63 65 ]. However, our study provides mixed support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that MPF would be associated with midlife obesity, given that it often involves an early age at first birth, high parity and multiple partnership dissolution—three factors that have been found to be independently associated to BMI as part of cardiovascular risk [ 8 , 9 , 11 , 26 , 63 65 ]. However, our study provides mixed support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) trial, a multicenter study in Germany that studied patients with CAD and analyzed the social and economic status of the studied population, concluded that women with lower levels of education had less social and emotional support, while academic men had the most [40]. Following the practical implications of social status, specifically marital status, there is a meaningful influence on the severity of the condition in females; an observational, multicenter study reported that there is a significant association between divorce and severe multivessel disease, or left main disease, in women [41].…”
Section: Potential Biological and Sociocultural Factorsmentioning
confidence: 99%
“…(2017) [41] The observational, multicenter study focused on establishing the relationship between divorce and the severity of CAD, MVD, and LMD in men and women.…”
Section: Dreyer Et Al (2015) [39]mentioning
confidence: 99%